2005
DOI: 10.1183/09031936.05.00006005
|View full text |Cite
|
Sign up to set email alerts
|

T-helper cell type-2 regulation in allergic disease

Abstract: Substantial experimental evidence now supports the notion that allergic diseases are characterised by a skewing of the immune system towards a T-helper cell type-2 (Th2) phenotype.Studies using both human and mouse model systems have provided key evidence for the role that Th2 cytokines play in driving many of the hallmarks of allergic inflammation. Furthermore, the signalling pathways by which Th2 cytokines exert their effects on airway target cells are rapidly being elucidated, and antagonists of the Th2 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 239 publications
(241 reference statements)
1
101
0
4
Order By: Relevance
“…16 Various studies have shown a strong association between fibrogenesis, a hallmark of PTCB, and the development of a T H 2 CD4 inflammatory response that involves IL-4 and IL-13. [17][18][19][20] Given the fact that PTCB is a form of chronic GVHD of the lung it is plausible that it is a T H 2-mediated disease, which may explain the clinical response we observed to inhaled corticosteroids. Furthermore, airway fibrosis can explain the limited improvement in FEV1.…”
Section: Discussionmentioning
confidence: 55%
“…16 Various studies have shown a strong association between fibrogenesis, a hallmark of PTCB, and the development of a T H 2 CD4 inflammatory response that involves IL-4 and IL-13. [17][18][19][20] Given the fact that PTCB is a form of chronic GVHD of the lung it is plausible that it is a T H 2-mediated disease, which may explain the clinical response we observed to inhaled corticosteroids. Furthermore, airway fibrosis can explain the limited improvement in FEV1.…”
Section: Discussionmentioning
confidence: 55%
“…PGE 2 has been reported to have other actions, e.g. suppressing dendritic cell leukotriene B 4 secretion by an IL-10-dependent mechanism (22) . The enzyme pathways that metabolise arachidonic acid also metabolise n-3 PUFA such as EPA to 3-series PG and 5-series leukotrienes that possess biological activity, albeit less potent than arachidonic acid metabolites.…”
Section: Pufamentioning
confidence: 99%
“…Cytokines such as IL-4, IL-5 and IL-13 secreted by Th2 cells are important mediators of asthmatic and allergic inflammation that is characterised by elevated IgE, mastcell degranulation and eosinophilic inflammation (4,5) . There is increasing interest in the role of regulatory T-cells in the pathogenesis of asthma and allergic disease because of their ability to directly inhibit both Th1 and Th2 responses (6) .…”
mentioning
confidence: 99%
“…Also epigenetic mechanisms have been invoked in the promotion of asthma phenotypes such as exposure to methyl-rich diets which can affect asthma risk in offspring (64) . From an immunological point of view, asthma is characterised by a hyperactivation of Th-2 cells, IgE production and eosinophilia (65) . Besides secretion of conventional cytokines, such as IL-4, IL-5 and IL-13, release of IL-17 from Th-17 cells gives rise to respiratory neutrophilic inflammation in the asthmatic patients (65,66) .…”
Section: Asthmamentioning
confidence: 99%
“…From an immunological point of view, asthma is characterised by a hyperactivation of Th-2 cells, IgE production and eosinophilia (65) . Besides secretion of conventional cytokines, such as IL-4, IL-5 and IL-13, release of IL-17 from Th-17 cells gives rise to respiratory neutrophilic inflammation in the asthmatic patients (65,66) . Treg cell deficits have been discovered in atopic allergic diseases, even including asthma (67) .…”
Section: Asthmamentioning
confidence: 99%